Bi-cruciate substituting total knee arthroplasty improved medio-lateral instability in mid-flexion range - Kaneko, Takao (J Orthop, 2017)
PURPOSE: Appropriate medio-lateral (ML) stability is an important factor of good clinical outcome following total knee arthroplasty (TKA). We hypothesized that a newly introduced Bi-Cruciate Stabilized substituting (BCS) prosthesis reduces the medio-lateral instability in mid-flexion range. The purpose of this study was to measure the ML stability (varus ligament balance) using a new tensor device after implantation of BCS TKA and to analysis the association between varus ligament balance and clinical results after TKA. MATERIALS AND METHODS: We evaluated 33 patients who underwent 39 Journey. 2. BCS TKA using the measured resection technique. We measured the gaps after implantation from extension to full flexion with reduced patella by constant distraction force with 120N. The varus ligament balance gap was defined as the gap calculated by subtracting from Lateral to medial component gap. The clinical results at 2years after operation was compared with intraoperative varus ligament balance. RESULTS: Varus ligament balance showed its maximum gap at full knee extension and 120° flexion. Varus ligament balance at 30°, 60° and 90° of flexion were significant differences in the varus ligament balance at full extension. (* p < 0.05). The varus ligament balance gap was negatively corrected with postoperative 2011 Knee society score (patient’s satisfaction) (r = 0.661, p = 0.001). CONCLUSIONS: The most important findings of the present study are that BCS TKA can reduces the ML instability in mid-flexion range, and improve simultaneously the patient’s satisfaction. LEVEL OF EVIDENCE: Therapeutic study, Level III.